Taxonomic contribution to the knowledge of the genus Indoribates and Lauritzenia (Acari, Oribatida, Haplozetidae), with description of a new species from China - Xu, Shu-Jing; Liu, Cheng-Lin; Chen, Jun (Zootaxa, 2024)
Oribatid species from China of the genus Indoribates and Lauritzenia are studied, with description of a new species Indoribates (Indoribates) subiasi sp. nov. based on adult materials collected from China. Indoribates (I.) japonicus (Aoki, 1988), I. (Haplozetes) vindobonensis curtipilis (Kunst, 1977), and Lauritzenia (Incabates) nuda (Hammer, 1961), are recorded in China for the first time. A new combination is proposed: Lauritzenia (Incabates) nobilis (Golosova, 1984) comb. nov. (from the genus Cosmobates Balogh, 1959). Two new synonyms are proposed: Indoribates (Haplozetes) vindobonensis curtipilis (= Haplozetes ulykpani Bayartogtokh & Aoki, 1998 syn. nov.) and Indoribates (Indoribates) Jacot, 1929 (= Indoribates (Bihaplozetes) Subías, 2020 syn. nov.). A key to the known species of Indoribates and Lauritzenia from China is also provided.